Feminist Choices of Early Women Bible Translators - Willett, Elizabeth Ann Remington (Open theology, 2016)
Translations by two early women Bible translators, Julia E. Smith (1792-1886) and Helen Barrett Montgomery (1861-1934), reflect their difference in purpose in attempting the translations as well as their level of knowledge of translation theory and linguistics. Smith translated merely for personal use in her own small society; her major concern was faithfulness to what she termed "the literal meaning." Montgomery, on the other hand, wrote in consideration of her audience; she wanted to communicate clearly and naturally in idiomatic terms. Smith was inward-focused, whereas Montgomery was outward-focused.